2017
DOI: 10.4081/ejh.2017.2763
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cytoskeleton features and maturation status of cultured human iPSC-derived cardiomyocytes

Abstract: Recent innovations in stem cell technologies and the availability of human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) have opened new possibilities for studies and drug testing on human cardiomyocytes in vitro. Still, there are concerns about the precise nature of such ‘reprogrammed’ cells. We have performed an investigation using immunocytochemistry and confocal microscopy on several cellular features using commercially available hiPSC-CMs. For some selected developmentally regulated or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…This is in agreement with numerous studies showing that the differentiation status of CMs generated from stem cells resemble an embryonic or neonatal state [4,21,22]. The average sarcomere length in iPSC-derived CM is about 1.84 µm, which corresponds to former reports showing that the distance between two adjacent sarcomeres is~1.7-2.0 µm (Figure 2) [14,16,23]. This large variety in sarcomere length, observed in several studies, might be attributed to different imaging techniques used, causing varying extents of artefacts [24,25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with numerous studies showing that the differentiation status of CMs generated from stem cells resemble an embryonic or neonatal state [4,21,22]. The average sarcomere length in iPSC-derived CM is about 1.84 µm, which corresponds to former reports showing that the distance between two adjacent sarcomeres is~1.7-2.0 µm (Figure 2) [14,16,23]. This large variety in sarcomere length, observed in several studies, might be attributed to different imaging techniques used, causing varying extents of artefacts [24,25].…”
Section: Discussionsupporting
confidence: 92%
“…To evaluate the structural maturation of iPSC CMs, cells are usually subjected to microscopic approaches that allow the quantification of sarcomere organization and alignment [14][15][16]. While electron microscopy provides high spatial resolution, sample preparation and image acquisition is complex and extensive user skills are required.…”
Section: Introductionmentioning
confidence: 99%
“…The intermediate filament protein vimentin was used as marker for cardiac fibroblasts because it is expressed in both quiescent and activated cardiac fibroblasts in vitro and in vivo (Ali et al, 2014;Kofron et al, 2017). Vimentin is not found in freshly isolated adult rat cardiomyocytes, but it is expressed to some extent in 2D cultured hiPSC-CMs as we have previously shown (Zuppinger et al, 2017). Using cryosections of adult murine left ventricle we examined the distribution and morphology of cardiac fibroblasts in normal murine ventricular tissue (Figure 2A).…”
Section: Immunocytochemical Characterization Of Cardiomyocytes and Cfmentioning
confidence: 90%
“…For the identification of hiPSC-CMs in 2D-and 3D cultures we used sarcomeric proteins that are well-organized at this stage in hiPSC-CM in 2D culture and in cardiac spheroids (Beauchamp et al, 2015;Zuppinger et al, 2017). The intermediate filament protein vimentin was used as marker for cardiac fibroblasts because it is expressed in both quiescent and activated cardiac fibroblasts in vitro and in vivo (Ali et al, 2014;Kofron et al, 2017).…”
Section: Immunocytochemical Characterization Of Cardiomyocytes and Cfmentioning
confidence: 99%
“…Myofibrils and sarcomeres are mature indicators related to the contraction force of cardiomyocytes [35,36]. Ultrastructural characterization by TEM demonstrated that histamine treatment showed better-organized cross-striated myofilaments and more mitochondria in hiPSC-CMs on day 18 compared with those in the control group (Fig.…”
Section: Histamine Facilitates the Maturation Of Cardiomyocytes Derivmentioning
confidence: 93%